Therapeutic Role of Samjnasthapana Mahakashaya Siddha Ghrita in Phubbing - A Single-Arm Interventional Study in Young Adults - M. K. Sarada; B. M. Shreevathsa (Journal of Ayurveda, 2025)
Introduction: Phubbing, a behavioral pattern characterized by excessive smartphone engagement at the expense of interpersonal interactions, has emerged as a significant concern in the digital era. From a classical perspective, it can be understood as a derangement in Samjna, impacting Chetana, Indriya Karma, and Manas. This study aimed to evaluate the efficacy of Samjnasthapana Mahakashaya Siddha Ghrita in restoring Samjna balance and mitigating phubbing tendencies.